تأثير العوامل البصرية والمعلوماتية للتعبئة والتغليف على القرار الشرائي للمستهلك - الهام، بن منصور; أحمد، سماحي (جامعة عمار ثليجي بالأغواط, 2016)
في ظل ما يشهده الاقتصاد الجزائري حالياً من تغيرات متسارعة، نتيجة لما أفرزته العولمة بمظاهرها المختلفة من زيادة في حجم المبادلات التجارية وحرية انتقال مختلف المنتجات في الأسواق، أدى إلى اشتداد المنافسة بين المؤسسات المتواجدة في السوق المحلية مما دفع بها إلى إحداث تغييرات جذرية للتكيف مع محيطها والبقاء والاستمرار عبر تكثيف جهودها للوصول إلى تلبية وحاجات ورغبات المستهلك الذي يعتبر محور النشاط التسويقي، وعليه نجد من أهم السياسات والاستراتيجيات التي تقدم عليها المؤسسات الإنتاجية سياسة التعبئة والتغليف، حيث أصبح التغليف جزءاً أساسياً من حياتنا المعاصرة. فقد تطور دور التعبئة والتغليف مع توسع الأسواق وخاصةً في الدول المتقدمة باعتباره أحد المكونات الأساسية للمنتج الذي يعمل على تعزيز صورته الذهنية لدى المستهلك، حيث اعتبره العديد من مفكري التسويق أحد قضايا التخطيط الاستراتيجي للمنتج، فقد تجاوز دوره الوظائف التقنية ليرتقي إلى الدور الترويجي في مواقع البيع بالاعتماد على العناصر التي يجملها سواء البصرية والمعلوماتية، والتي تعمل على رسم وترسيخ صورة المنتج في ذاكرة المستهلك.
In light of what is currently witnessing the Algerian economy of rapid changes as a result of what was produced by globalization, the various manifestations of an increase in the volume of trade and freedom of various transmission products in the markets, led to the intensification of competition between existing institutions in the domestic market, prompting them to bring about radical changes to adapt to their surroundings and stay and continue through to intensify its efforts to gain access to meet the needs of the consumer, which is the focus of marketing activity and desires. Accordingly, we find the most important policies and strategies that provide them productive enterprises packaging policy, where packaging has become an essential part of our modern life.. It has developed the role of packaging with the expansion of markets, especially in developed countries as one of the basic ingredients of the product, which works to promote mental image among consumers. Where many considered one of the thinkers of marketing and strategic planning issues for the product has exceeded his role technical jobs to move up to the promotional role in Short positions depending on the elements carried by both visual and information and working to draw and consolidate the product image in the consumer memory.
Keywords: المؤسسات الإقتصادية -- التسويق -- التعبئة و التغليف -- المستهلك -- الشراء